Factors affecting the integration of one stop crisis centre (OSCC) in Penang - Oon, Siti Waringin (2018)
This study identify the factors affecting the integration of One Stop Crisis Centre (OSCC) and explores the idea and working concept of integration for OSCC from the perspectives of the stakeholders including service providers, clients and policy makers/key informants. A qualitative methodology was applied in this study and face to face interview was carried out to fourty-four respondents. They were twenty eight service providers from various agencies related to OSCC, ten clients who were ever attended the services and six key informants who were the pioneer and at the policy makers level of the setup of OSCC. The results of the study indicate that OSCC has not achieved the level of integration and still working at the coordination level. There are six elements that affect the integration to happen include the attitude and knowledge of the staff, communication, key personnel, standardised guidelines, accountability and accessibility of the services of which OSCC is still trying to achieve. In addition, the findings revealed two emerging elements that should be considered for the integration of the OSCC to happen, that is, by having a champion or key driver and communication and this can contribute to the conceptual model. Important conclusion drawn from this study is that the integration of the OSCC services requires the empowerment of agencies involved and adjustments to barriers at system level in order for the services to empower women and community on the issue of VAW. A comprehensive health services suchas OSCC has the potential to significantly sustain and improve the services to respond to VAW.